2016
DOI: 10.1007/s00204-016-1775-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Nrf2 signaling pathway in usnic acid-induced toxicity in HepG2 cells

Abstract: Many usnic acid-containing dietary supplements have been marketed as weight loss agents, although severe hepatotoxicity and acute liver failure have been associated with their overuse. Our previous mechanistic studies revealed that autophagy, disturbance of calcium homeostasis, and ER stress are involved in usnic acid-induced toxicity. In this study, we investigated the role of oxidative stress and the Nrf2 signaling pathway in usnic acid-induced toxicity in HepG2 cells. We found that a 24-h treatment with usn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…Previous studies demonstrated that several key mechanisms of drug induced liver toxicity such as mitochondrial dysfunction, apoptosis, and ER stress are mediated by the MAPK signaling pathway (Chen et al, 2017; Ren et al, 2016). In the current study, another important finding is that the activation of JNK and ERK1/2, two branches of the MAPK cascade, contributes to the toxicity of leflunomide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that several key mechanisms of drug induced liver toxicity such as mitochondrial dysfunction, apoptosis, and ER stress are mediated by the MAPK signaling pathway (Chen et al, 2017; Ren et al, 2016). In the current study, another important finding is that the activation of JNK and ERK1/2, two branches of the MAPK cascade, contributes to the toxicity of leflunomide.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq libraries were constructed and sequenced using the TruSeq protocol on an Illumina HiSeq 2000 platform. Data analysis was as described previously (Chen et al, 2017). The read counts for each sample were normalized as reads per million mapped reads (RPM) and transformed to log 2 scale for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS production was measured as described previously (Chen et al 2017). Briefly, cells were seeded in 96-well plates; after 12 h, cells were treated with 10 μM H 2 DCF-DA for 45 min at 37 °C in the dark, and then they were washed with PBS to remove unincorporated dye.…”
Section: Methodsmentioning
confidence: 99%
“…To explore further the possible mechanisms of DNA damage induced by dronedarone, we assessed the generation of reactive oxygen species (ROS), which has been Environmental and Molecular Mutagenesis. DOI 10.1002/em recognized as a prominent trigger of DNA damage (Evans and Cooke, 2004;Chen et al, 2017). No significant alternation of intracellular ROS level was observed in dronedarone treated cells as measured by H 2 DCFDA staining (data not shown).…”
Section: Dronedarone Downregulates the Expression Of Topoisomerase IImentioning
confidence: 89%
“…DOI 10.1002/em recognized as a prominent trigger of DNA damage (Evans and Cooke, 2004;Chen et al, 2017). DOI 10.1002/em recognized as a prominent trigger of DNA damage (Evans and Cooke, 2004;Chen et al, 2017).…”
Section: Dronedarone Downregulates the Expression Of Topoisomerase IImentioning
confidence: 99%